(untitled) (Stavební obzor - Civil Engineering Journal, 2015)
The silos are widely used in bulk material in many fields such as agriculture, mining, chemical, electric power storage, etc. Thin metal cylindrical silo shells are vulnerable to buckling failure caused by the compressive wall friction force. In this paper, the structural analysis of two types of steel silo with cylindrical-wall bearing and profile-steel bearing is implemented by Abaqus finite element analysis. The results indicate that under the same loading conditions, steel silos with profile-steel bearing and cylindrical-Wall bearing have similar values in Mises stress, but the steel silo with profile-steel bearing has a smaller radial displacement and a better capability of buckling resistance. Meanwhile, the total steel volumes reduced 8.0% comparing to the steel silo with cylindrical-wall bearing. Therefore, steel soil with profile-steel bearing not only has a less steel volumes but also a good stability.